Managing Digital Ethics: A Local Wisdom-Based Model for Cyberbullying Prevention in Islamic Educational Institutions - Syarkawi, Syarkawi; Hamsidar, Hamsidar; Najmuddin, Najmuddin; Rizal, Muhammad (JURNAL AL-TANZIM, 2026)
Cyberbullying has become a critical challenge in the digital era, threatening adolescents’ mental health and emotional development. This study aims to examine how cyberbullying prevention is implemented in Islamic boarding schools through local wisdom–based management and value internalization. Using a qualitative phenomenological design, data were collected from boarding school leaders, teachers, caregivers, and students through in-depth interviews, observations, and document analysis, and analyzed using NVivo-assisted thematic coding. The findings reveal that cyberbullying prevention is institutionally structured through four management functions: planning, organizing, actuating, and controlling, with actuating emerging as the most dominant function (51% of coded references). Prevention practices are operationalized through daily habituation, integration of digital ethics into religious instruction, and moral-spiritual supervision. Additionally, Acehnese local wisdom values such as Meuseuraya, Tameusaboh, Seumapa, Peumulia Jamee, and Adat Bak Poe Teumeureuhom are embedded as behavioral regulators in both offline and online interactions. This study contributes a culturally grounded cyberbullying prevention model that integrates educational management, local wisdom, and Islamic values. The findings suggest that sustainable digital ethics education should prioritize moral internalization and community-based supervision.